2002
DOI: 10.4269/ajtmh.2002.66.787
|View full text |Cite
|
Sign up to set email alerts
|

Intra-familial and extra-familial risk factors associated with Cryptosporidium parvum infection among children hospitalized for diarrhea in Goiânia, Goiás, Brazil.

Abstract: Abstract.A cross-sectional study was conducted for assessing the prevalence of and risk factors associated with Cryptosporidium parvum in diarrheic children who were hospitalized in Goiânia, capital of Goiás State in Brazil. A crude prevalence of 14.4% (64 of 445) was observed using a direct immunfluorescent assay (DFA), but the true prevalence was 18.7% (83 of 445) when a gold standard of immunomagnetic separation was used in combination with the DFA. Infection was more predominant in children less than 24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
30
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
(51 reference statements)
7
30
3
10
Order By: Relevance
“…In cryptosporidiosis surveillance, the proportion of females was found to be 1.15 times higher in females as compared to males [25]. However, Pereira et al (2002) have also shown that the risk of infection among male patients was 2.2 times higher as compared to that in females among children hospitalized for diarrhea in Brazil. Kimani et al (2012) have observed the proportion of males to be 3.35 times higher as compared to that of females in a study conducted at Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…In cryptosporidiosis surveillance, the proportion of females was found to be 1.15 times higher in females as compared to males [25]. However, Pereira et al (2002) have also shown that the risk of infection among male patients was 2.2 times higher as compared to that in females among children hospitalized for diarrhea in Brazil. Kimani et al (2012) have observed the proportion of males to be 3.35 times higher as compared to that of females in a study conducted at Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Timely studies conducted in urban and rural areas identified prevalence rates ranging from 0.03% to 12.9%, with the highest rates being in children attending daycare centers (GONÇALVES et al, 2006;ANARUMA FILHO et al, 2007;BRANCO et al, 2011;LANDER et al, 2012;ROLANDO et al, 2012). However, in children with diarrhea, the prevalence tends to increase, with rates ranging from 18.7% to 32.4% (PEREIRA et al, 2002;NASCIMENTO et al, 2009). Most of the Brazilian studies used optical microscopy combined with differential color methods as a screening method for Cryptosporidium spp., which has low sensitivity compared to molecular techniques (ELSAFI et al, 2013).…”
Section: Epidemiological Aspects Of Human Cryptosporidiosismentioning
confidence: 99%
“…O rotavírus é o principal agente viral relacionado à diarreia aguda infantil 10 , no entanto outros vírus, como norovírus e astrovírus, são responsáveis por casos isolados de diarreia aguda 11 e por surtos 12 . Entre os protozoários, Cryptosporidium, Giardia lamblia e Entamoeba histolytica 13,14,15 são os mais comuns relacionados aos quadros diarreicos infantis. A frequência destes enteropatógenos torna-se elevada em crianças de baixa renda que vivem em condições sanitárias insatisfatórias, diferentemente do que acontece com os vírus que podem ser encontrados associados à diarreia aguda independente da situação econômica ou social da população 16 .…”
unclassified